Reforma agrária e desenvolvimento sustentável? A difícil construção de um assentamento rural agroecológico em Ribeirão Preto - SP - Gonçalves, José Cláudio (2010)
The question of rural development has been discussed by different agencies and agents, governmental or otherwise, that directed the discussions towards convergence between the questions of agriculture, agrarian and environment. In this approach, the conservation and restoration of natural resources are considered as important as the agricultural production. In Brazil, this approach has placed the agrarian reform settlements as areas important for the implementation of agricultural projects based on environmental sustainability. The case study we developed in a rural settlement in the municipality on the Ribeirão Preto, region northeastern state of Sao Paulo shows that the implementation of such projects exacerbates conflicts between the agents and expressed the fragmentation and dislocation of public policies for rural settlements. Comparing the different discourse and practices, we aimed to understand what is an environmental sustainability for the state, social movements and rural workers settled.